Case report: Fatal Legionella infection diagnosed via by metagenomic next-generation sequencing in a patient with chronic myeloid leukemia - Bu, Chunhong; Lei, Shuai; Chen, Linguang; Xie, Yanqiu; Zheng, Guoli; Hua, Liwei (Frontiers in Medicine, 2023)
Legionella is an aerobic, gram-negative, intracellular pathogen and is an important cause of community-acquired pneumonia. Legionella pneumophila is the most common causative agent of Legionella pneumonia. Clinical diagnosis of Legionella pneumonia is challenging due to the lack of specific clinical manifestations and the low positive rates of conventional pathogen detection methods. In this study, we report a case of a patient with chronic myeloid leukemia who developed rigors and high fever after chemotherapy and immunotherapy. Chest computed tomography revealed consolidation in the left lower lobe of the lung and ground-glass opacities in both lower lobes. Multiple blood cultures showed Escherichia coli, Staphylococcus aureus, Bacillus licheniformis, and positive results in the β-D-glucan test (G test). The patient was treated with various sensitive antimicrobial agents, including meropenem plus fluconazole, meropenem plus carpofungin, and vancomycin. Unfortunately, the patient’s condition gradually worsened and eventually resulted in death. On the following day of death, metagenomic next-generation sequencing (mNGS) of 1whole blood revealed L. pneumophila pneumonia with concurrent bloodstream infection (blood mNGS reads 114,302). These findings suggest that when conventional empirical antimicrobial therapy proves ineffective for critically ill patients with pneumonia, the possibility of combined Legionella infection must be considered, and mNGS can provide a diagnostic tool in such cases.